[3+2] Cycloaddition of Propargylic Alcohols and α‐Oxo Ketene Dithioacetals: Synthesis of Functionalized Cyclopentadienes and Further Application in a Diels–Alder Reaction1. (30th May 2014) - Fang, Zhongxue; Liu, Jianquan; Liu, Qun; Bi, Xihe
Abstract Cyclopentadienes are valuable intermediates in organic synthesis and also ubiquitous as the Cp ligands in organometallic chemistry. As part of ongoing efforts to develop novel organic reactions that employ functionalized alkynes, a [3+2] cycloaddition of propargylic alcohols and ketene dithioacetals has been developed, which leads to fully substituted 2, 5‐dialkylthio cyclopentadienes in good to excellent yields. In an unusual dethiolating Diels–Alder reaction, the cyclopentadienes were further reacted with maleimides to afford a family of novel fluorescent polycyclic compounds.